OPTIMALISASI PENGUASAAN ENGLISH VOCABULARY MELALUI PEMANFAATAN MEDIA LUDO WORDS GAME (LWG) PADA SISWA SEKOLAH DASAR - SUHARDIANA, I PUTU ANDRE (Institut Hindu Dharma Negeri Denpasar, 2017)
Education is surely an important tool in creating qualified human resources. It could be formed when applying education as the key to the development of science and technology. In the Standards of Content published by the The National Agency for Educational Standards (BSNP), English language subject in elementary schools is directed at developing four skills, namely, listening, speaking, reading, and writing skills as a means of communicating and discourse in English at a certain literacy level. English language education in primary school, according to the Standards of Content, of The National Agency for Educational Standards (BSNP) has the intention to develop language skills used in accompanying the action. Building a vocabulary, in this case, is the main thing in learning a foreign language at an elementary school level. Vocabulary not only builds reading skills but also other skills. At a certain level, when students can develop their vocabulary mastery, they will automatically improve themselves on listening, speaking, reading, and writing skills. Utilization of Ludo Word Game media in order to optimize the mastery of English vocabulary in elementary school students is actually a Ludo game which has been modified in such a way, which has a purpose to improve the mastery of English vocabulary. In addition, students' creativity in learning can also be developed automatically by collaborating the pictures card media on this learning media.